ADMINISTRACIÓN DE TESTOSTERONA EN ALPACAS CON ADHERENCIAS PENE-PREPUCIALES - San Miguel S., Celestina (2002)
In order to study the effect of testosterone on penis-prepucial adherences,twenty alpacas were selected from a flock of male tuis. Fourteen and six of the selected animals were one and two years old respectively, from which 90% showed almost complete penis-prepucial adherence (0 and 1 grade) and the remaining showed a grade 2 adherence. Animals were randomly assigned to two treatment groups (Toand T2) according to age and adherence grade in order to achieve experimental equilibrium. Each T2 animal received 327 mg of testosterone i.m. distributed in three doses,on a two-week interval. Both body weight and adherence releasing grade were evaluated fortnightly; testicular size and sexual behaviour were recorded weekly. A larger releasing adherence was observed in one-year-old alpacas in T2, specially between weeks sixth and ninth, after treatment (P<0.08). There was a treatment-age interaction(P<0.05)in body weight, in which one-year-old alpacas from T2had higher body weight gain than those from T0(P<0.05), and than those of two-year-old alpacas from T0 and T2(P<0.01). Treatment-age interaction was also significative on testicular size(P<0.05) because of alarger increase in length and width in one-year-old males from T0than in the other animals(P<0.01), while the smallest increase(P<0.01) was showed by one-year-old males from T0 and T2. Sexual behaviour was absent in almost all males exposed to females in heat.